Etiology of Allergic Contact Dermatitis based on Patch Test - Dita Maulida Anggraini; Endang Sutedja; Achadiyani Achadiyani (Althea Medical Journal, 2017)
Background: Allergic contact dermatitis is a type of contact dermatitis, whose  prevalence tends to increase every year. Patch test is an important diagnostic test to confirm the disease. The result of patch test can help doctors to perform appropriate treatment.  The aim of the study was to identify  the most frequent allergen causing allergic contact dermatitis based on patch test results.Methods: This was a descriptive retrospective study among patients who underwent patch test at the Dermatology and Venereology Clinic in Dr.Hasan Sadikin General Hospital Bandung, Indonesia from August 1st, 2014 to August 31st, 2015. The patch test result was obtained from the patient’s medical record and recapitulation data. The patient’s medical record would be collected based on inclusion and exclusion criteria. This study also collected demographic data of the patients, including age, sex, and occupation.The collected data were presented using tables.Results: Out of 45 patient’s medical records, 19 patients were male (42.2%) and 26 patients were female (57.8%). Nickel sulphate was the most frequent allergen with 17 sensitization. Thirteen out of 17 patients who were sensitized by nickel sulphate were females. A great majority of the patients were in the age group of 15–44 years. Most of the patients were students (42.2%). Allergic contact dermatitis (64.4%) was the main clinical diagnosis among the patients.Conclusions: The most frequent allergen causes allergic contact dermatitis is nickel sulphate.